2009
DOI: 10.3109/08860220903100705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Myocardial Remodeling in Hemodialysis Patients

Abstract: Background. Left ventricular hypertrophy (LVH) is an independent risk factor for morbidity/mortality in patients with end stage renal disease (ESRD). Our study aimed to identify prevalence as well as independent risk factors that contribute to the development of LV geometric remodeling in our HD patients. Methods. The left ventricles of 116 HD patients were classified echocardiographically into four different geometric patterns on the basis of LV mass and relative wall thickness. Furthermore, we measured infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…Renal insufficiency is a known risk factor for heart failure [23], diastolic dysfunction, and LV remodeling [24]. The risk of cardiovascular remodeling attributable to mild-to-moderate renal insufficiency may not be fully captured by current estimates of renal function such as creatinine, GFR, and creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Renal insufficiency is a known risk factor for heart failure [23], diastolic dysfunction, and LV remodeling [24]. The risk of cardiovascular remodeling attributable to mild-to-moderate renal insufficiency may not be fully captured by current estimates of renal function such as creatinine, GFR, and creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal LV geometry is widespread in renal patients . While most studies, but not all, reported that cLVH predominates in non–dialysis‐dependent (NDD)‐CKD, eLVH appears most prevalent in CKD5D . Primarily subjects with cLVH, who carry a high risk of stroke, may suffer from the combined deleterious effects of the biochemical and circulatory alterations that occur during the transition from advanced CKD to early CKD5D .…”
Section: Introductionmentioning
confidence: 99%
“…3 While most studies, 3,6-8 but not all, 9 reported that cLVH predominates in non-dialysis-dependent (NDD)-CKD, eLVH appears most prevalent in CKD5D. 10,11 Primarily subjects with cLVH, who carry a high risk of stroke, 12 may suffer from the combined deleterious effects of the biochemical and circulatory alterations that occur during the transition from advanced CKD to early CKD5D. 13 Moreover, LV features may change over time as observed both in participants of the Framingham Heart Study (FHS) 14 and CKD patients stage 3 to 4 who took part of the Cardiovascular Risk reduction by Early Anemia Treatment with Epoietin beta (CREATE) trial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that increased IDWG[18] is a risk factor for low QoL scores. Increased IDWG predisposes the patient to rapid and large-volume ultrafiltration with its associated intradialytic hypotension, cramps, dialysis-related headache,[1920] interdialytic hypertension[21] and left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%